2017
DOI: 10.1080/10942912.2017.1289387
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform mid-infrared spectroscopy and chemometrics to identify and discriminate Boletus edulis and Boletus tomentipes mushrooms

Abstract: Boletus edulis and Boletus tomentipes are two well-known mushroom species which are widely consumed in Yunnan province due to their high nutritional and medicinal values. Fourier transform mid-infrared spectroscopy can determine exclusive spectra fingerprint of a sample and further analyse its quality when combined with appropriate chemometrics. In this study, identification and discrimination of B. edulis and B. tomentipes mushrooms from different geographical locations were performed based on Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Hence, it seems important to take initiatives for the sustainable use of this species. For this, spectroscopic techniques can be used to classify samples of any type due to its speed and simplicity, and its low-cost approach (Qi et al, 2017). For example, Fourier transform midinfrared (FT-MIR) spectroscopy is an effective tool which can scan the chemical composition of a sample in the mid-infrared region (4000 to 400 cm −1 ) and the fingerprint region created by this technique can give information on the sample's certainty quality (Grunert et al, 2016;Muhtar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it seems important to take initiatives for the sustainable use of this species. For this, spectroscopic techniques can be used to classify samples of any type due to its speed and simplicity, and its low-cost approach (Qi et al, 2017). For example, Fourier transform midinfrared (FT-MIR) spectroscopy is an effective tool which can scan the chemical composition of a sample in the mid-infrared region (4000 to 400 cm −1 ) and the fingerprint region created by this technique can give information on the sample's certainty quality (Grunert et al, 2016;Muhtar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared (FT-IR) spectroscopy, the traditional technique espoused by the high sensitivity of conformational change and high-quality spectra, has been validated that it was a powerful tool for metabolite analysis of mushrooms (Baltacıoglu, Bayındırlı, Severcan, & Severcan, 2015;Ma et al, 2018;O'Gorman, Downey, Gowen, Barry-Ryan, & Frias, 2010). In the study of Qi, Zhang, Liu, Li, and Wang (2017), they identified B. edulis and B. tomentipes stemmed from different geographical origins using FT-IR combined with chemometrics including principal component analysis (PCA), partial least squares-discriminant analysis (PLS-DA), and hierarchical cluster analysis (HCA). Comprised of FT-IR spectra and other analytical techniques, there also other published literatures concerning about discrimination research using data fusion strategy which is an extension of the study mentioned above (Qi, Li, Liu, Li, & Wang, 2018;Yao, Li, Li, Liu, & Wang, 2018a;Yao, Li, Liu, Li, & Wang, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…To date, various analytical approaches have been implemented to determine important components or metabolic fingerprints to analyze the quality of plants and food [ 13 , 14 , 15 , 16 ]. Many sensor systems have also been well conducted for the discrimination of mushrooms according to different microhabitats.…”
Section: Introductionmentioning
confidence: 99%